Assessment of mucosal pH of saliva in patients with oral lichen planus: A case-control study - Naveen Kumar; Shilpa P Shastry; T K Rama Murthy; S Nikhitha; B S Mahesh; Usha Dayanarayana (Wolters Kluwer Medknow Publications, 2023)
Background: Salivary flow rate, buffering capacity, and pH are significant salivary parameters that assist in maintaining oral equilibrium and act as a barrier of protection against an array of maxillofacial diseases. Oral lichen planus (OLP) is a chronic inflammatory disease that causes severe oral mucosal soreness, including burning and itching sensation, and management of certain cases is challenging due to multifactorial reasons. Therefore, probing for a factor that may cause alterations in the characteristics of lichen planus is important. Very few studies have been conducted concerning the changes in the salivary parameters and OLP. pH of saliva is one such salivary parameter. Objectives: To determine the mucosal pH of saliva affected by OLP and healthy volunteers followed by comparing the difference between the mucosal pH of healthy oral mucosa and oral mucosa affected by OLP. Methods: pH strips were used to assess the pH of saliva in OLP patients and healthy volunteers. Results: The analyzed data showed statistically significant differences in the mean pH of patients with OLP when compared to that of the normal healthy controls. Conclusion: pH plays a significant role in maintaining the equilibrium of oral health. Therefore, its alteration may indirectly affect the disease and its treatment outcomes.